Determination of Antiradical Activity, Total Phenolic, and Total Flavonoid Contents of Extracts and Fractions of Langsat (Lansium domesticum Coor.) Seeds - Yamin Yamin; Ruslin Ruslin; Sabarudin Sabarudin; Nurramadhani A Sida; Henny Kasmawati; La Ode Muhammad Diman (Borneo Journal of Pharmacy, 2020)
Lansium domesticum Coor. is a fruit species from the Meliaceae family, which is a tropical plant native to Southeast Asia. Local citizens call it langsat, longkong, or duku and have used it as traditional medicine. The seeds of L. domesticum are used as a fever medicine, its bark is used to treat scorpion sting, and its leaves are used to repel mosquitoes. Because of its various uses, it is necessary to explore the antiradical potential of L. domesticum seeds. This study aims to determine the antiradical potential of L. domesticum seeds extract and fractions by using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and to discover compounds that act as antiradical. Lansium domesticum seed powder was macerated with methanol, and then the extract was concentrated using a rotary evaporator and fractionated by n-hexane and ethyl acetate. The antiradical assay was conducted on extract and fractions by using DPPH radicals. Phenolic and flavonoid contents from extract and fractions were also tested. The ethyl acetate fraction obtained strong antiradical potential with an IC50 value of 8.938 ± 0.031 µg/mL. Total phenolic and flavonoid contents of ethyl acetate fraction were higher with values ​​of 58.25 ± 0.501 mgGAE/g sample and 75.123 ± 0.175 mgQE/g sample, respectively. Correlation of phenolic and flavonoid contents, which inhibited radicals had R2 values ​​of 0.9182 and 0.7658. Ethyl acetate fraction of L. domesticum seeds had very strong antiradical activity. Further isolation is expected to be conducted to discover which compounds are the most responsible as antiradical.